Treatment patterns for chronic obstructive pulmonary disease under the tiered medical system - Xiaoli Wang; Xingru Zhao; Tianqi Cen; Yi Yu; Zhiwei Xu; Lijun Shen; Ziqi Wang; Paul Jones; Quncheng Zhang; Yunxia An; Xiaoju Zhang (Scientific Reports)
Abstract China has implemented the “tiered medical services” policy since 2015, while there is a paucity of data evaluating the the current status of chronic obstructive pulmonary disease (COPD) management under the system. Characteristics and treatments from 11,905 COPD patients in 88 hospitals across different tiers in China were included and analyzed. We assessed the statistical significance of differences by one way analysis of variance (ANOVA) for continuous variables and with the chi-squared test for categorical variables. Patients in primary hospitals (Tier1) exhibited heightened exposure to risk factors including smoking, household biofuel, and family history of respiratory diseases, and displayed elevated COPD assessment test (CAT) and modified Medical Research Council (mMRC) dyspnea scale scores, and worse lung function, in comparison to tertiary (Tier3) hospitals (P < 0.001). However, the utilization of inhaled maintenance treatments in Tier1 hospitals is markedly lower than that in Tier3 hospitals (54.8% vs. 81.3%, P < 0.001). At odds with the patients with more severer symptoms (as indicated by CAT ≥ 10 or mMRC ≥ 2), a higher proportion relied exclusively on single bronchodilators in Tier1 hospitals was observed compared to secondary (Tier2) and Tier3 hospitals (37.7% vs. 32.1% vs. 26.3%, 40.0% vs. 29.8% vs. 25.6%, P<0.001). Dual bronchodilators (long-acting β2-agonists /long-acting muscarinic antagonist, LABA/LAMA) represented the least common medication regimen across all tiers of hospitals, albeit their usage rates increased in tandem with hospital tier (0.7% vs. 7.2% vs. 10.4%, P < 0.001). In addition, the use of inhalation therapies containing inhaled corticosteroids (ICS) in China’s primary care is notably lower (16.9%) than the United States, the United Kingdom, and other middle-to-high-income countries (29.5-57.0%). There was compelling evidence pointing to greater disease severity in Tier1 hospitals, attributable to the lower and inappropriate utilization of inhaled maintenance treatments. This underscores the necessity for enhanced availability of medications and educational initiatives aimed at both physicians and patients within Tier1 hospitals.